Student Teams Achievement Division Learning Model: Learning Outcomes of Pancasila Education at Primary School - Vina Rimarsia Tetiwar; Fransheine Rumtutuly; Stelie Dorce Ratumanan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Low student learning outcomes in Pancasila Education are often triggered by the use of learning models that are less varied and passive. This study aims to improve learning outcomes in Pancasila Education through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model in fifth-grade students of Primary School 2 Tiakur. The method used is Classroom Action Research (CAR) which is implemented in two cycles, covering the cognitive, psychomotor, and affective domains. Data were collected through observation and learning outcome tests, then analyzed descriptively comparatively. The results of the study showed significant improvements at each stage. In the pre-cycle stage, the average class score was only 56 with a classical completion of 12%. After the implementation of cycle I, the average score increased to 67 with a completeness of 28%, but did not reach the established success indicator. Improvement actions in cycle II through intensification of group guidance, optimization of time management, revision of LKPD, and giving meaningful awards succeeded in increasing the average score to 82 with a classical completion of 96% (24 out of 25 students). The conclusion of this study is that the STAD model is effective in improving student learning outcomes holistically and exceeding established success indicators. This research contribution provides a practical reference for educators regarding strategies for strengthening student competencies in the Pancasila Education curriculum through structured cooperative learning.